Improving the Strength Properties of Kaolinite Type Clays Using Melamine Formaldehyde Liquid Polymer - Altuğ Saygılı (Doğal Afetler ve Çevre Dergisi)
Soil remediation methods have become one of the preferred methods due to the need for more space for construction activities in cities and industrial areas. Another reason for choosing the remediation techniques is to obtain economical and faster solutions compared to the conventional methods. In recent years, the use of chemical stabilizers in soil remediation applications, such as slope stability, erosion and bearing capacity, has increased steadily due to economy, easy application, workability and early strength gain. In this study, the effects of liquid melamine formaldehyde polymer on the strength properties of kaolinite type clay were investigated. The changes in compressive strength values were evaluated by adding liquid melamine formaldehyde polymer into the kaolinite specimens compacted at previously determined optimum water content value. The liquid polymer was added at 3, 6, 9 and 12 per cent by weight with water, so as not to exceed the optimum water content of the matrix, and the prepared polymer-added samples were cured for 3, 7, 14 and 28 days to observe the strength gain at different curing times. Significant increases were observed in the strength values of the samples stabilized with different percentages of liquid polymer subjected to unconfined compression tests at the end of the curing period as the polymer addition ratio and the curing time increased. According to the obtained results, melamine formaldehyde liquid polymer can be applied to clayey soils as a soil stabilizer.